Effect of crystallinity on the recovery rate of superhydrophobicity in plasma-nanostructured polymers - Oh, Ji-Hyun; Moon, Myoung-Woon; Park, Chung Hee (ROYAL SOC CHEMISTRY, 2020)
This study explored the optimum conditions to achieve superhydrophobicity in polyethylene terephthalate (PET) in terms of crystallinity and microstructure. Surface superhydrophobicity was achieved by nanostructures induced by oxygen plasma etching and the recovery process of low surface energy through thermal aging of various PETs; semi-crystalline biaxial PET (B-PET) film, amorphous PET (A-PET) film, and semi-crystalline PET (F-PET) fabric. Under the anisotropic plasma etching, the nanostructures on the B-PET film were the longest, followed by the F-PET fabric, which developed a hierarchical micro/nanostructure, then the A-PET film. During thermal aging at 80 degrees C near T-g, the plasma-treated A-PET film recovered its superhydrophobicity within 3 h, while the plasma-treated B-PET film did not exhibit superhydrophobicity. At 130 degrees C, higher than T-g, the plasma-treated B-PET film recovered its superhydrophobicity within 1 h, but the plasma-treated A-PET film became opaque as its nanostructures deformed, decreasing its superhydrophobicity. The plasma-treated F-PET fabric exhibited faster recovery and greater superhydrophobicity than the plasma-treated B-PET film, due to its hierarchical micro/nanostructure. In addition, hydrophobic recovery during thermal aging was proved with a decrease in surface polar groups, lowering the surface energy using XPS analysis. Therefore, by designing the ratio of crystal to amorphous regions and surface micro/nanostructures, one can rapidly fabricate superhydrophobic PETs without additional surface finishing.
Keywords: THERMOMECHANICAL ANALYSIS; PET FILMS; POLY(ETHYLENE-TEREPHTHALATE); WETTABILITY; POLYPROPYLENE; ORIENTATION; TEMPERATURE; FABRICATION; INTERFACE; MOISTURE